A colisão de princípios na vedação do direito de greve aos militares - Horszczaruk, Jean Pedro (My University, 2021)
This Course Conclusion Paper will aim to analyze the conflict between fundamental rights to the right to strike and its constitutional prohibition in relation to the military, seeking to ascertain the preponderance between constitutional principles such as the Supremacy of the Public Interest, Isonomy and Dignity of the Human Person. For that, it is necessary the individual analysis of the strike institutes, essential public services and the career and duties of the military. Considering that both rights are linked to the guarantee of the principle of the dignity of the human person, it is essential to reconcile the pillars of the continuity of the public service and the right to strike. Afterwards, the application of the principle of supremacy of the public interest to the detriment of Isonomy will be analyzed, as will the losses for the category that has misrepresented a fundamental constitutional right. Finally, an analysis will be made of decisions made by the Supreme Federal Court and repercussions of movements already observed in the scope of the search for rights by the military, in order to examine the solution found in the specific cases for the collision of fundamental rights under study. Understanding that a constitutional amendment is feasible, in order to eliminate the amendment that brings the prohibition of the right to strike and consequently the notable attack on therights of a category. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso terá como objetivo analisar o conflito entre os direitos fundamentais ao direito de greve e a vedação constitucional deste em relação aos militares, buscando averiguar a preponderância entre princípios constitucionais como Supremacia do Interesse Público, Isonomia e Dignidade da Pessoa Humana. Para isso, fazem-se necessárias a análise individual dos institutos da greve, serviços públicos essenciais e da carreira e atribuições dos militares. Considerando que ambos os direitos estão ligados à garantia do princípio da dignidade da pessoa humana, é imprescindível a conciliação entre os pilares da continuidade do serviço público e o direito de greve. Após, será analisada a aplicação do princípio da supremacia do interesse público em detrimento da Isonomia, tal quais os prejuízos para a categoria que tem deturpado um direito fundamental constitucional. Por fim, será feito uma análise de decisões proferidas pelo Supremo Tribunal Federal e repercussão de movimentos já constatados no âmbito de busca por direitos por parte dos militares, a fim de examinar a solução encontrada nos casos concretos para a colisão dos direitos fundamentais em estudo. Entendendo que é viável uma alteração constitucional, a fim de eliminar a emenda que traz a vedação do direito de greve e consequentemente o notável ataque aos direitos de uma categoria. [resumo fornecido pelo autor]
Keywords: Direitos fundamentais; Greves e lockouts; Serviço público; Direito constitucional